2018
DOI: 10.1111/jcpt.12712
|View full text |Cite
|
Sign up to set email alerts
|

Improving medication safety for home nursing clients: A prospective observational study of a novel clinical pharmacy service-The Visiting Pharmacist (ViP) study

Abstract: Integrating pharmacists into a home nursing service identified and addressed MRPs and medication treatment authorization discrepancies, hence contributing to enhanced medication safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 28 publications
(99 reference statements)
1
31
0
Order By: Relevance
“…However, this participation rate was comparable to 10-12% participation rates reported in studies of pharmacist medication management services for community-dwelling adults in Australia and the United Kingdom. 37,38 Higher recruitment rates of 31-39% have been achieved when referrals are made by a person's usual pharmacist or GP. 39,40 Process barriers to recruitment included the amount of recruitment For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…However, this participation rate was comparable to 10-12% participation rates reported in studies of pharmacist medication management services for community-dwelling adults in Australia and the United Kingdom. 37,38 Higher recruitment rates of 31-39% have been achieved when referrals are made by a person's usual pharmacist or GP. 39,40 Process barriers to recruitment included the amount of recruitment For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides some of the first qualitative data from home care that explain many of the medication management challenges home care providers face when working with medically complex older adults. With medication management and education part of the core HHC quality indicators, this data shed an explanatory light on many findings from quantitative research studies that have highlighted medication management issues in HHC (Caughey et al, 2019;Feldman, Bridges, & Peng, 2007;Gershon et al, 2012;Kollerup et al, 2018;Lang et al, 2015;C. Y. Lee et al, 2018;Marck et al, 2010;McDonald et al, 2016;Miner et al, 2017;Piras, Miele, Bruni, Coletta, & Zanutto, 2014;Rose, Jaehde, & Köberlein-Neu, 2018;Woerner, Espinosa, Bourne, O'Toole, & Ingersoll, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…This leads to situations where community nurses sometimes work with multiple orders, in multiple formats, from multiple prescribers . Our research has found that fewer than 20% of home nursing clients have a medication chart, up to 31% have multiple medication orders used concurrently and 72.6% of medication orders contain one or more discrepancy compared with a pharmacist‐obtained medication history that was verified using multiple sources …”
Section: Introductionmentioning
confidence: 96%
“…It has also been reported that approximately 30%–50% of home nursing clients are prescribed potentially unnecessary or inappropriate medications, highlighting a need for medication review and deprescribing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation